Orange-fleshed Sweetpotato on the School Feeding Program in Osun State, Nigeria - International Potato Center (2017)
Starting in January 2015, orange-fleshed sweetpotato (OFSP) was included on the menu once a week at 8 schools in 8 Local Government Areas (LGAs) of Osun State, Nigeria. In September 2015, the number of schools was increased to 17, and by December 2016, the total increased to 186 schools in 24 out of 31 LGAs. Local farmers supplied over 10 tons of OFSP weekly to feed 41,426 pupils, about 16% of the State’s 254,000 students in primary classes 1 through 4. State agencies such as the Osun Youth Empowerment Scheme (O-YES) are encouraging youth to take up sweetpotato production and marketing to serve all of the State’s schools.